2019
DOI: 10.1177/0885066619892826
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation in Pregnant and Postpartum Women: A Systematic Review and Meta-Regression Analysis

Abstract: Background: Although extracorporeal membrane oxygenation (ECMO) is frequently utilized as a salvage therapy for patients with cardiopulmonary failure, outcomes of its use in peripartum patients have not been clearly established. We aimed to review peer-reviewed publications on the use of ECMO in pregnant and postpartum patients, with analyses of maternal and fetal outcomes. Methods: Data were retrieved from MEDLINE, EMBASE, and Scopus databases from 1972 up to November 2017 for publications on ECMO in peripart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 37 publications
1
38
2
Order By: Relevance
“…were included in our meta-analysis. Case reports and series with a sample size of <5 were excluded per recommendations by the Cochrane Statistical Methods Group and in accordance with methodologies of previously published meta-analyses [7][8][9]. Other exclusion Table 2].…”
Section: Study Selectionmentioning
confidence: 99%
“…were included in our meta-analysis. Case reports and series with a sample size of <5 were excluded per recommendations by the Cochrane Statistical Methods Group and in accordance with methodologies of previously published meta-analyses [7][8][9]. Other exclusion Table 2].…”
Section: Study Selectionmentioning
confidence: 99%
“…As a high degree of inter-study heterogeneity was expected, random effects meta-analyses (DerSimonian and Laird) [ 18 , 19 ] were conducted on R 3.6.1 using the meta (v4.12-0) and dmetar (v0.0.9000) packages, and confidence intervals (CI) were computed using the Clopper–Pearson method [ 20 ]. Mortality outcomes are presented as pooled proportions and 95% confidence intervals (CI), and dichotomous outcomes are presented as odds ratios (ORs) and 95% CI.…”
Section: Methodsmentioning
confidence: 99%
“…Planned subgroup analyses were conducted with continuity correction to allow the inclusion of studies with zero events and included the other reported mortalities (in-hospital, ICU, 30-day or 90-day), the geographical location (Asia, Europe, America, and Australia), the presence of renal replacement therapy (RRT and no RRT), the duration ECMO (more and less than 7 days) and the year of publication (before and after 2016). Summary-level meta-regression was conducted if a minimum of 6 data points could be collected to explore potential sources of heterogeneity or prognostically-relevant study-level covariates [ 18 ]. We used the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) guidance to assess between-study heterogeneity and rated the certainty of evidence using the GRADE approach [ 21 , 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…A minimum sample size of 4 was implemented in accordance with the methodologies of previously published meta-analyses. 21 , 22 The quality of included studies was assessed using the Joanna Briggs Institute (JBI) checklist for prevalence studies and the JBI checklist for case series.…”
Section: Methodsmentioning
confidence: 99%